APPLICATION OF ITERATIVE DYNAMIC PROGRAMMING TO OPTIMAL FEED-BACK CONTROL PROBLEM - A. V. Panteleev; D. A. Rodionova (Научный вестник МГТУ ГА)
This paper presents a generalization of iterative dynamic programming using Luus-Jakola optimization procedure applied to the solution of optimal feed-back control for nonlinear deterministic systems. Iterative dynamic programming is realized. Efficiency of proposed method is tested on the software complex developed by the authors in C++; a model example of chemical process control is presented.